Ibn Hazm's methodology of Jahala in his book Al-Muhalla - Abdulqader, Fareed Mohamed Hadi (The University of Edinburgh, 2000)
This thesis is a study of Ibn Hazm's methodology of rejecting narrations, in particular where he judges the narrators to be unknown (majhul). It examines:

1. Ibn Hazm's methodology of jahala.

2. Ibn Hazm's agreement and disagreement with the Hadlth scholars in judging narrators to be unknown (majhul).

3. The impact of Ibn Hazm's judgement of unknown narrators upon his jurisprudence.

The thesis contains an introduction, three parts and a conclusion. In the introduction the significance of the research and the necessity for the study are explained.

Part One deals with Ibn Hazm and the Zahirl school and contains two chapters. Chapter 1 covers Ibn Hazm's personal and scholarly life, and Chapter 2 studies the Zahiri school, its influence and its principles.

Part Two studies Ibn Hazm's rejection of narrations for reasons other than jahala and is divided into three chapters. Chapter 3 focuses on Ibn Hazm's criticism of narrators as weak or liars; Chapter 4 explains Ibn Hazm's criteria for rejecting narrations; and Chapter 5 examines Ibn Hazm's criticism of chain and text.

Part Three, which is the main part of the study, covers Ibn Hazm's methodology of jahala and its effect on rejecting narrators and narrations. It contains five chapters. Chapter 6 explains 'adala andjahala according to the scholars' definitions. Chapter 7 examines the opinions of Ibn Hazm and other scholars with regard to unknown narrators. Chapter 8 covers Ibn Hazm's method of assessing narrators' 'adala ('adalat al-ruwat). Chapter 9 examines Ibn Hazm's judgement of narrators in his book Al-Muhalla in order to clarify his method of assessing jahala. Chapter 10 examines Ibn Hazm's judgement of narrators as being unknown and its impact upon his jurisprudence.

Finally, the conclusion summarizes the discussions of the thesis and presents the findings of the study.